Identifying patient-level health and social care costs for older adults discharged from acute medical units in England - Franklin, Matthew; Berdunov, Vladislav; Edmans, Judi; Conroy, Simon; Gladman, John R.F.; Tanajewski, Lukasz; Gkountouras, Georgios; Elliott, Rachel A. (Oxford University Press, 2014)
Background: Acute medical units allow for those who need admission to be correctly identified, and for those who could be managed in ambulatory settings to be discharged. However, readmission rates for older people following discharge from acute medical units are high and may be associated with substantial health and social care costs. Objective: Identifying patient-level health and social care costs for older people discharged from acute medical units in England. Design: Prospective cohort study of health and social care resource use. Setting: An acute medical unit in Nottingham, England. Participants: 456 people aged over 70 who were discharged from an acute medical unit within 72 hours of admission. Methods: Hospitalisation and social care data were collected for three months post-recruitment. In Nottingham, further approvals were gained to obtain data from general practices, ambulance services, intermediate care and mental healthcare. Resource use was combined with national unit costs. Results: Costs from all sectors were available for 250 participants. Mean (95% CI, median, range) total cost was £1926 (1579-2383, 659, 0-23612). Contribution was: secondary care (76.1%), primary care (10.9%), ambulance service (0.7%), intermediate care (0.2%), mental healthcare (2.1%) and social care (10.0%). The costliest 10% of participants accounted for 50% of the cost. Conclusions: This study highlights the costs accrued by older people discharged from AMUs: they are mainly (76%) in secondary care and half of all costs were incurred by a minority of participants (10%).